PENGARUH EARNING DAN DIVIDEN TERHADAP HARGA SAHAM (STUDY KASUS PADA SUBSEKTOR TEKSTIL DAN GARMEN) - Endah Dewi Purnamasari; Nabila Nur Rahmah (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2021)
If a company has a high stock return, the higher the probability of earning the profit. High stock returns are referred to as Earning Per Share (EPS). The stock price will also increase due to an increase and offer of a share. Companies must strive to provide high dividend profits so that the company's share price also increases. If it cannot offer significant dividends, the stock price may decline on the contrary. In the F-test, the significance value is 0.000. A deal that shows < 0.05 means that the hypothesis accepted a significant influence between EPS and stock dividends on the company's stock price in the textile and garment sub-sector for 2016 to 2020. And on the T-test, the results of the significant number are < from 0, 05 are 0.04 and 0.05. it concluded that in the T-test, the test result rejected H1, and H2 was accepted. Then the final result shows that there is no significant effect between Earning Per Share and Dividend per share on stock prices.